Application Development of Baihui (GV20) Moxibustion in Ancient China: a Data Analysis Study Based on Ancient Books - Ma Yueying; Chen Liming; Qu Changcheng; Ji Jun (Medical Association of Pharmacopuncture Institute, 2024)
Importance: We compile and analyze ancient literature related to Baihui (GV20) moxibustion and summarize the development of its ancient clinical application.Observations: The Chinese Medical Classic (5th edition) was used as the search source to screen and organize articles related to Baihui moxibustion to establish a database. We created indexing norms according to study characteristics and indexed books, dynasties, literary styles, disease key words, matching acupoints, combinations, moxibustion amounts, and moxa cone sizes. SPSS version 24.0 software was used to calculate the index results. A total of 320 articles that met the requirements were finally included and were attributed to 99 ancient books, spanning from the Western Han Dynasty to the Qing Dynasty. A total of 45 keywords were used for disease evidence: the most frequent occurrences were internal medicine (primary category), limb meridians (secondary category), and head diseases (specific patterns).Conclusion : s and Relevance: Baihui moxibustion has been updated and developed in the literature over the ages, and the method of Baihui moxibustion is diverse. The main treatment rule of Baihui moxibustion considers the whole body and close treatment of partial diseases. Baihui moxibustion also has the rule of following meridian indications, with treatment based on syndrome differentiation and compatible application. Baihui moxibustion alone has a relatively strong effect of raising yang and lifting the sunken, which can treat the sinking of qi and deficiency.